Publication activity indicators of the Moscow Healthcare Department organizations in the subject area "Transplantation" - Aksenova, E. I.; Kamynina, N. N.; Tarkhov, K. Yu (Transplantologii͡a, 2023)
Background. Bibliographic analysis for the period 2017–2022 showed an extremely small number of literary sources (scientific publications) in both foreign and domestic periodicals, which would cover issues related to the consideration, study and/or analysis of any aspects of publication activity in the field of transplantology at the global, national and regional levels or in with respect to specific organizations, journals and authors. In Russian periodicals, the objects of research are often either various countries of the world (in comparative characteristics with Russia), or medical universities of the Russian Federation, or scientific medical organizations of federal designation, while there is a complete absence or a small number of publications devoted to the issues of publication activity of organizations at the level of the city of Moscow. Aim. Conducting a scientometric study to characterize, analyze and evaluate the publication activity of the Moscow Healthcare Department organizations in the subject area "Transplantation". Material and methods. The study was carried out for the subject area "Transplantation" using analytical platform SciVal for more than 10 quantitative and shared scientometric indicators (from 2019 to 2021) for 55 organizations from the categories of research institutes, scientific and practical centers and city clinical hospitals subordinated to the Moscow Healthcare Department. Results and discussion. The main scientometric indicators (in quantitative and fractional ratio) characterizing the publication activity over a three–year period – from 2019 to 2021 – in the subject area "Transplantation" in organizations subordinate to the Moscow Healthcare Department. Conclusion. It is shown that in the subject area "Transplantation" during the period under review, positive growth and changes in scientometric indicators such as the total number of publications, the number of publications in 1st–2 nd quartiles, the number of publications in national and intraorganizational collaboration are observed for the Moscow Healthcare Department organizations.